Inhibition of TRPM7 blocks MRTF/SRF-dependent transcriptional and tumorigenic activity - Voringer, Sandra; Schreyer, Laura; Nadolni, Wiebke; Meier, Melanie; Woerther, Katharina; Mittermeier, Constanze; Ferioli, Silvia; Singer, Stephan; Holzer, Kerstin; Zierler, Susanna; Chubanov, Vladimir; Liebl, Bernhard; et al. (Oncogene, 2019)
Myocardin-related transcription factors A and B (MRTFs) are coactivators of Serum Response Factor (SRF) that mediates the expression of genes involved in cell proliferation, migration and differentiation. There is mounting evidence that MRTFs and SRF represent promising targets for hepatocellular carcinoma (HCC) growth. Since MRTF-A nuclear localization is a prerequisite for its transcriptional activity and oncogenic properties, we searched for pharmacologically active compounds able to redistribute MRTF-A to the cytoplasm. We identified NS8593, a negative gating modulator of the transient receptor potential cation channel TRPM7, as a novel inhibitor of MRTF-A nuclear localization and transcriptional activity. Using a pharmacological approach and targeted genome editing, we investigated the functional contribution of TRPM7, a unique ion channel containing a serine-threonine kinase domain, to MRTF transcriptional and tumorigenic activity. We found that TRPM7 function regulates RhoA activity and subsequently actin polymerization, MRTF-A-Filamin A complex formation and MRTF-A/SRF target gene expression. Mechanistically, TRPM7 signaling relies on TRPM7 channel-mediated Mg2+ influx and phosphorylation of RhoA by TRPM7 kinase. Pharmacological blockade of TRPM7 results in oncogene-induced senescence of hepatocellular carcinoma (HCC) cells in vitro and in vivo in HCC xenografts. Hence, inhibition of the TRPM7/MRTF axis emerges as a promising strategy to curb HCC growth.
CRIS-Team Scopus Importer:2019-12-27